Communicating Nutrition and Other Science: A Reality Check. Issue 1 (January 2016) - Rowe, Sylvia B.; Alexander, Nick
Abstract : The authors take up an issue recently explored in the literature: the increasing exaggeration of research results in press releases and in the mass media. Pointing out that such exaggeration may stem from a fundamental misunderstanding of science as "magic, " rather than as a process of experimentation, they propose that nutrition communicators adopt a new perspective: acknowledgement that science progresses by trial and error rather than a search for "truth." They cite commentators who suggest banning such misleading expressions as "statistically significant, " "theory, " and "truth, " as well as such common nutrition science terms as "natural" and "organic." The authors recommend that nutrition communicators focus on telling their readers not about such fantasies as "super foods" and "life-prolonging supplements, " but about how better to think about health and nutrition science.